VSE Electrical Sdn. Bhd. / Izuarina Casandra Dorcas - Dorcas, Izuarina Casandra (Universiti Teknologi MARA, Sarawak, 2019)
VSE Electrical Sdn Bhd was incorporated in September 2009 as ELV supplier, system integrator and contractor. The company is located in Ground Floor, Lot 8306, Jalan Datuk Abang Abdul Rahim 7C, 93450 Kuching, Sarawak. The company provide professional services in system designs and equipment installation for Extra Low Voltage, Lighting, Audio Visual, Intelligence Smart Control and Digital Information Technology System. They also provide good after sales technical support for all our completed project and product sales. The company has a team of technical engineers and highly qualified personnel in implementing project management, equipment installation, configuration, testing and commissioning. The company have their own board of directors that responsible with the operations of the company. There are three main directors in the VSE Electrical Sdn Bhd which are Mr. Ho Wei Ming, Mr. Voong Sau Hui and Mr. Chin Wei Ming. Different directors will be in charge in different department. Mr. Ho Wei Ming is in charge as a leader of the Management team while Mr. Voong Sau Hui is in charge as a leader of Project Division team and Mr. Chin Wei Ming is in charge in the Sales Division. The company have several types of different division such as Management division, Engineering division, Cost And Design division, Support Service division, and Project division. Every each of the Division has their own manager that responsible to ensure all the operation process of the company runs smoothly as the company must ensure all the job done in the time frame provided as the company is a project based electrical company. The company have four main strengths which are the strength is manpower, experience, service and maintenance also strength in product range. As for the strength in manpower the company has over than fifty staff that are technical and skilful personnel. The Company also have the management group that has over 20 years of experience in this specialised industry. The company has successfully executed project throughout the whole Sarawak. Service and maintenance is also one of the strength of the company as they are committed and service oriented towards their customers. The strength of the company in product range is they has be able to carry a wide range of products ranging from high end quality to standard and economical range quality to suit with their customer various requirement.